Differential diagnosis of vascular structures in relation to upper ascending aorta: The retro-aortic innominate vein - Sukulal, Kiron (Medknow Publications & Media Pvt Ltd, 2013)
The retroaortic course of left innominate vein is a rare entity which can be misinterpreted during echocardiography for other abnormal vascular structures under the arch of aorta. We report the case of a 2 month old infant where the suprasternal window showed 2 vascular structures beneath the aortic arch, one of which was traced to be a retroaortic innominate vein.